An immunoproteomic approach for characterization of dormancy within Staphylococcus epidermidis biofilms. Issue 2 (June 2015) - Carvalhais, Virginia; Cerveira, Frederico; Vilanova, Manuel; Cerca, Nuno; Vitorino, Rui
Highlights Immunoproteomic pattern of S. epidermidis biofilms with induced and prevented dormancy. Proteins reactive to human sera were first separated by 2-DE. CodY and GpmA proteins were more reactive to sera when biofilm dormancy was induced. FtnA and ClpP proteins were more reactive when biofilm dormancy was prevented.